2018
DOI: 10.1016/j.ijscr.2018.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cavernous hemangioma after pelvic radiotherapy in a female patient: A case report and literature review

Abstract: Highlights The bladder cavernous hemangioma (BCH) is a benign non-urothelial tumor rarely occurred in the urinary bladder. Treatment options are vary for individuals and most are with favorable follow-ups. A history of cancer related radiation therapy seems to be a risk factor for BCH. It is important to differentiate them from malignant neoplasms since they have extremely different prognostic features and therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…UBHs are mostly congenital benign tumour formations of angiogenesis. Nevertheless, several studies have confirmed increased risks of developing soft tissue tumours related to radiation therapy for cancer[ 8 , 9 ]. The predominant clinical symptom of a UBH is the painless recurrence of isolated gross macroscopic haematuria with or without irritative urinary symptoms and abdominal pain[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UBHs are mostly congenital benign tumour formations of angiogenesis. Nevertheless, several studies have confirmed increased risks of developing soft tissue tumours related to radiation therapy for cancer[ 8 , 9 ]. The predominant clinical symptom of a UBH is the painless recurrence of isolated gross macroscopic haematuria with or without irritative urinary symptoms and abdominal pain[ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we conducted a thorough English literature review focusing on literature about UBHs published up to January 2019, and we identified 16 cases published from 2000 to 2019 after strict selection stored in the PubMed database (Table 1 )[ 5 , 6 , 9 , 12 - 22 ]. The following key words were used for literature retrieval: (“case report”) and (“Urinary Bladder Hemangioma” or “Bladder hemangioma” or “Hemangioma of the urinary bladder”).…”
Section: Discussionmentioning
confidence: 99%
“…UBH are mostly congenital benign tumor formations of angiogenesis. Nevertheless, several studies have con rmed increased risks of developing soft tissue tumors in relation to radiation therapy for cancer [8][9] . The predominant clinical symptom of UBH is painless recurrent, isolated gross macroscopic hematuria with or without irritative urinary symptoms and abdominal pain [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Bladder hemangiomas used to be diagnosed so rarely that we know of only several dozens of histologically verified cases in the late century.5 However, a timely diagnosis of hemangioma is important due to a positive prognosis comparing to muscle invasive bladder cancer.5 The conventional ways of surgical treatment of bladder hemangiomas include biopsy with or without fulguration, transurethral resection, partial cystectomy and embolization 5,6,911. The development of visualization techniques and physician awareness of hemangioma led to an increase in the number of case reports covering the application of new surgical methods 9,11. However, there are no clinical guidelines for large bladder hemangiomas.…”
Section: Discussionmentioning
confidence: 99%